2019
DOI: 10.3390/su11030906
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Changes and the Driving Forces of Sloping Farmland Areas in the Sichuan Region

Abstract: Sloping farmland is an essential type of the farmland resource in China. In the Sichuan province, livelihood security and social development are particularly sensitive to changes in the sloping farmland, due to the region's large portion of hilly territory and its over-dense population. In this study, we focused on spatiotemporal change of the sloping farmland and its driving forces in the Sichuan province. Sloping farmland areas were extracted from geographic data from digital elevation model (DEM) and land u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Expressly, changes in cultivated land in mountain areas are directly limited by local natural conditions and are also greatly affected by socioeconomic modes, policy implementation, and farmers' livelihoods (Li, Zinda, & Zhang, 2019). For instance, due to different interest objectives of policy implementation departments, social, economic, and agricultural intensification factors have significant differences on the impact of cultivated land undertaken on slopes at a prefecture‐level city in Sichuan Province (Xiao et al, 2019); 66.20% of the differences in cultivated land change drivers of Chongqing come from the district/county level (Song, Cao, Zhou, Su, & Qiu, 2020). Ultimately, human disturbance in terms of management has the most significant impact on the evolution of cultivated land (Liang, Li, & Zhou, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Expressly, changes in cultivated land in mountain areas are directly limited by local natural conditions and are also greatly affected by socioeconomic modes, policy implementation, and farmers' livelihoods (Li, Zinda, & Zhang, 2019). For instance, due to different interest objectives of policy implementation departments, social, economic, and agricultural intensification factors have significant differences on the impact of cultivated land undertaken on slopes at a prefecture‐level city in Sichuan Province (Xiao et al, 2019); 66.20% of the differences in cultivated land change drivers of Chongqing come from the district/county level (Song, Cao, Zhou, Su, & Qiu, 2020). Ultimately, human disturbance in terms of management has the most significant impact on the evolution of cultivated land (Liang, Li, & Zhou, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The areas of steep slope farmland (>25 • ) decreased by 302 km 2 , still accounting for the largest proportion of cultivated land area throughout the region. Terrain changes were the main cause of the reductions in the MCI in this region [55]. Furthermore, correlation analysis showed that there was a significant decreasing exponential relationship between the relief amplitude and MCI in the three provinces (y = 326.77e −0.01x , R 2 = 0.3336, P < 0.01), which further proved that the MCI decreased as the relief amplitude increased.…”
Section: The Influence Of Terrain Factors On the MCImentioning
confidence: 62%
“…As the accelerated urbanization has encroached on the cropland in the countryside surrounding cities and towns via construction, large amounts of farmland have been transferred from the south to the north [7], and from urbanizing areas, mostly in plain regions with high soil quality, to the remote rural hinterland with relatively low soil quality [8], that are unlikely to be occupied again by urban expansion and human activities. This continuous land-use transformation is associated with an increasing amount of sloping cropland [9], which is defined as cropland with a slope greater than 2 • [10]. Studies have shown that sloping cropland has become a crucial resource for grain production [10][11][12] and maintaining people's basic livelihoods [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This continuous land-use transformation is associated with an increasing amount of sloping cropland [9], which is defined as cropland with a slope greater than 2 • [10]. Studies have shown that sloping cropland has become a crucial resource for grain production [10][11][12] and maintaining people's basic livelihoods [13,14]. It is widely recognized that an increase in the slope gradient results in more surface runoff and soil loss [12,15], causing lower soil fertility and a higher risk of eutrophication in rivers, lakes, and coastal areas [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation